THU0018 Angiotensinogen as a marker of injury in lupus nephritis. (15th June 2017) - Mas, LA; Retamozo, S; Salinas, MJ Haye; Saurit, V; Palomino, EV; Fuente, JL De la; Angelina, M; Pirola, JP; Alvarellos, A; Alvarellos, T
Abstract : Background: Lupus Nephritis (LN) is one of the most severe forms of systemic lupus erythematosus (SLE) (1). Angiotensinogen (AGT) gene encodes the only glycoprotein known to be a precursor of the vasopresor angiotensin II (Ang II). Ang II is also a growth factor and a profibrogenic cytokine (2). In kidney transplantation AGT has been founded down expressed in biopsies with chronic allograft dysfunction (3). In LN, AGT deserves evaluation. Objectives: To investigate AGT expression in biopsies and urines from LN patients. Methods: 32 biopsies/urines paired from 32 LN patients was included. Kidney biopsies were evaluated according to the ISN/RPS classification system. Levels of AGT were evaluated using Quantitative Real Time PCR. Threshold cycle (Ct ) scores were averaged for calculations of relative expression values. The Ct scores were normalized against Ct scores by subtracting β2Microglobuline control, or ΔCt=Ct, gene - Ct, B2M . Data expressed as ΔCt are inversely proportional to gene expression level. Nonparametric Mann Whitney test analysis and Anova with Bonferroni test were performed. Results: 26 (81.3%) patients were female with a mean age at biopsy time of 31.9±29 years. The SLEDAI at the time of biopsy was 10.5 (IQR 0–15.7) and SLICC ≥1 in 13 (32.5%), hypocomplementemia 13/31 (41.9%) and positive DNA in 11/29 (37.9%) patients. Biopsies from patients with proteinuria ≥0.5 and renal failure (n=23), proteinuria isolated (n=14), LN remission (n=9), renal failure (n=7) and nephrotic syndrome (n=2) were performed. The mean value of ΔCt AGT gene expression in renal biopsy was 4.50 (IQR 3.51 – 5.67) and AGT in urine samples was 13.94 (IQR 11.66 – 17.89). Conclusions: In the present study we found a potential utility of AGT mRNA levels in samples of active vs remission LN patients. Prospective studies are needed for confirming these results. References: Yajuan Li et al. Biomarkers Profiling for Lupus Nephritis. Genomics Proteomics Bioinformatics 11; 158–165, 2013. Eriguchi M et al. Assessment of urinary angiotensinogen as a marker of podocyte injury in proteinuric nephropathies. Am J Physiol Renal Physiol 310: F322–F333, 2016. Mas V et al. Establishing the molecular pathways involved in chronic allograft nephropathy for testing new non-invasive diagnostic markers. Transplantation. 83:448–57, 2007. Disclosure of Interest: None declared